Inflation and Monetary Policy: What South African Newspapers Report in an Era of Policy Transparency. Issue 3 (2nd July 2020) - Reid, Monique; Bergman, Zinette; Plessis, Stan Du; Bergman, Manfred Max; Siklos, Pierre
Abstract : Inflation is a monetary policy outcome, but in the short to medium term, price and wage decisions are co-determined by the public and private sectors. Many central banks have adopted transparency as a strategic policy approach, whereby communication of monetary policy goals is used as a public anchor. While the central bank's strategy involves carefully crafted, deliberately simplified messages, most of the public tends to access inflation-related information through the media. In this article, we examine South African newspaper articles to identify how inflation is presented in the media and the role of the media, through this presentation, in the process of shaping public opinion around inflation expectations. We do this in two ways. First, we examine how inflation is presented in the media and then we identify the various actors presented in the media, their positions on inflation, and how these relate to each other. The systematic analysis of the media's presentation of inflation allows us to identify some challenges to the central bank's communication strategy.